PLURALISME: MERAJUT IDENTITAS YANG TERKOYAK - Rahimal Khair; YUSRI HAMZANI (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2023)
This article discusses the concept of pluralaslime. In this article, the main problem studied is the level of religious pluralism in Indonesia. To get some data in this research method is to read and collect both primary and secondary references such as books, scientific articles, theses, dissertations, encyclopedias, internet and other sources. After conducting an in-depth analysis, the author finds that our plurality identity is being severely tested, especially after the Ahok case. The Ahok case created a new order in the midst of the religious community. Attitudes of exclusivity appear everywhere. To anticipate the collapse of brotherhood between religious communities, it takes an attitude to understand and understand each other. In addition, an attitude of inclusiveness is an attitude that must be applied in every element of society so that anarchism does not occur in the midst of a plural society.